Development ofcontact spot′s area at macrorunning in of friction surfaces / T. Zamota, V. Aulin // Problems of Tribology. – 2012. – № 1. – P. 9-13. - Замота, Т.Н.; Аулин, В.В. (Problems of Tribology, 2014)
The results of theoretical research of development of contact spot′s area at macrorunning in of friction surfaces are presented in the article. Development of contact spot′s area is considered on the running in detail from a primary contact to maximally possible taking into account the type of tribounit of details and size of macrogeometrical rejection.